An Evaluation of the Antidiabetic and Antimicrobial Activity of an Ethanolic Extract from Rhizophora mucronata Leaf - Usman Usman; Pintaka Kusumaningtyas; Sukemi Sukemi; Erwin Erwin (Jurnal Sains dan Kesehatan, 2023)
The aim of this research was to determine the antidiabetic and antimicrobial properties of ethanolic extract of Rhizophora mucronata leaves, as well as the phytochemical elements contained in the leaf extract. Extracts from R. mucronata leaf samples were obtained by maceration in ethanol-based solvents. The ethanolic extract of R. mucronata leaves is known to have an antidiabetic effect on mice, evidenced by its ability to reduce blood glucose levels. Giving ethanol extract at a dose of 600 mg/kg BW gives the greatest antidiabetic effect. The antibacterial activity of the extract against the tested bacteria and fungi was also limited due to the presence of contaminants in the ethanolic extract. The analysis of secondary metabolites using LC-MS revealed that the ethanolic extract of R. mucronata leaves contained 25 different secondary metabolite compounds. Furthermore research to purify and identify the compounds in the ethanolic extract of R. mucronata is required to develop this resource as an antimicrobial and antidiabetic drug based on natural materials.